Traditional Vernacular Architecture of Kumaon: The Case of the Hill Towns of Munsiyari, Uttarakhand - Neelima Yadav (INTBAU Spain, 2021)
Munsiyari is a region located at an altitude of 2,200 meters in the hilly state of Uttarakhand, India. The eponymous town is surrounded by twenty-two villages mostly inhabited by Bhotiya tribes, who once formed a community that traded with those crossing from India to Tibet, though this trade came to an abrupt end with the 1962 Sino-Indian war. Owing to the region’s prosperity, the villages exhibit a very interesting typology of hill architecture. This architectural identity is also a manifestation of a geographical and cultural response to a difficult terrain. Our study was carried out as part of the preparation of a dossier for inventorying the Kailash sacred landscape with the aim of documenting the present state of the traditional vernacular heritage of the selected indigenous community for the UNESCO nomination of the wider region. That thorough documentation process was used as a means of analyzing local vernacular heritage and its current situation, and with a view to offsetting the rapid transformation of the past two decades.